(untitled) (Revista de Medicina Clinica, 2023)
Letter to the editor on "Multiple Cavernomatous Cerebral Malformation in Pediatric Patient with Epilepsy" presented in Volume 7 Issue 1 of 2023 of JRevista de Medicina Clínica